Diseño de un sistema costos por proceso y su incidencia en la rentabilidad de la ebanistería “Márquez” del cantón la maná provincia de Cotopaxi periodo 2020. - Cando Veintimilla, Elsa Yolanda (2021)
This paper shows the results of the research conducted within the Marquez Cabinetmaking’s shop, with the objective of designing a process costing system and its impact on profitability in this shop in La Maná, province of Cotopaxi in 2020. The main research problem is that the cabinetmaking shop does not have a costing system to identify whether the prices of the products it offers are in line with the market and thus be able to know if it has an acceptable profitability. The manufacturing process of the goods made by the company goes through four production phases, each of which must identify the costs incurred in production. A process costing system is used in manufacturing industries to determine the total costs of producing a unit of product. It is particularly used in environments where the creation goes through multiple processes. The methodology used in the research project, related to the development of a manual of production process costs and its impact on profitability, emphasized a qualitative and quantitative approach, descriptive because it allowed us to know what is the current situation that the cabinetmaking is going through, from the results obtained it was concluded that to manufacture a bed, a door, a closet and a modular requires an amount of $ 30,695.89 In this way it was possible to know exactly the prices of the products.